(untitled) (E Global Congress, 2025)
Measurement of bending areas on the front and back surfaces. This is the most common method. This method is quite simple and reliable. A magnifying glass and an instrumentation microscope are used for measurement. Bending areas are photographed on the ground of the camera. The depth of the pit on the front surface is measured with an indicator attached to the pole. This method makes it possible to compare the effect of cutting tool geometry and cutting speed on bending within a unit of time.